A Simple Method for Cleaning Graphene Surfaces with an Electrostatic Force. (22nd October 2013) - Choi, Won Jin; Chung, Yoon Jang; Park, Serin; Yang, Cheol‐Soo; Lee, Young Kuk; An, Ki‐Seok; Lee, You‐Seop; Lee, Jeong‐O
Abstract : A facile method involving electrostatic forces is used to clean graphene surfaces that have been prepared through chemical vapor deposition (CVD). In this electrostatic‐force cleaning (EFC) method, extremely fine cloth fibers are rubbed against CVD‐grown graphene, in order to remove residual poly(methyl methacrylate) (PMMA), known as "PMMA‐G, " without damaging the graphene surface.